Basalt fiber composite material with bismuth oxyhalide growing on surface as well as preparation method and application of basalt fiber composite material
By growing bismuth oxyhalide of nanoparticle size on the surface of basalt fibers and performing ion exchange, the problem of degradation of mechanical properties when loaded on basalt fibers in the prior art is solved, and the mechanical properties of basalt fiber composites are improved and the application expansion is achieved.
Patent Information
- Application Number
- CN202411839188.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
When the prior art loads bismuth oxyhalide on basalt fibers, there are problems such as reduced mechanical properties, weak binding force, complicated preparation process and low ion utilization rate in the precursor solution.
The nanoparticle-sized bismuth oxyhalide oxyhalide surface is directly grown on the surface of the basalt fiber by hydrothermal method or solvothermal method, and the mechanical properties of the basalt fiber are improved through ion exchange, and a basalt fiber composite material with bismuth oxyhalide surface grown is prepared.
It significantly improves the tensile strength and elastic modulus of basalt fibers, and expands its application potential in the fields of environmental governance and composite materials.
Smart Images

Figure CN119702016A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of basalt fiber, and in particular to a basalt fiber composite material with bismuth oxyhalide grown on the surface thereof, and a preparation method and application thereof. Background Art
[0002] Basalt fiber is a high-performance inorganic fiber material made by melting and drawing natural basalt rock at high temperature. Basalt is a volcanic rock widely distributed on the earth. After processing, it can produce fibers with excellent properties. Basalt fiber is similar to glass fiber, but it has better mechanical strength, high temperature resistance, corrosion resistance and environmental friendliness. Therefore, it is widely used in fiber-reinforced composite materials, high-temperature filtration, sound absorption and noise reduction. However, the mechanical properties of basalt fiber still have room for improvement in some high-strength and high-modulus applications.
[0003] Bismuth oxyhalide (BiOX, X = Cl, Br, I) is a type of bismuth oxyhalide. 3 Layered photocatalytic materials composed of bismuth + and halogen anions (Cl-, Br-, I-) have shown wide application potential in many fields in recent years, especially in environmental governance, energy conversion and sensors. Loading bismuth oxyhalide on fibers has been a research hotspot in recent years. How to combine bismuth oxyhalide nanoparticles with photoelectric properties with basalt fibers to obtain basalt fibers with photoelectric functional properties is the key to introducing basalt fibers into applications such as environmental governance and composite materials.
[0004] At present, some scholars use hydrothermal / solvothermal method and continuous ion layer adsorption method to load bismuth oxyhalide on fibers. However, the high temperature and high pressure environment of the hydrothermal / solvothermal method will reduce the mechanical properties of the fiber. The continuous ion layer method has the disadvantages of weak bonding between semiconductor and fiber and complicated and time-consuming preparation process. In addition, a large number of ions in the precursor solution cannot be effectively utilized. Therefore, how to improve the recyclability of bismuth oxyhalide through modification, improve the utilization rate of ions in the precursor solution, and enhance the mechanical properties of the fiber while growing bismuth oxyhalide on the surface has become an important research topic. Summary of the invention
[0005] Therefore, in order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a basalt fiber composite material with bismuth oxyhalide grown on the surface, and a preparation method and application thereof. Bismuth oxyhalide with a nanometer particle size is directly grown on the surface of basalt fiber by a hydrothermal method or a solvothermal method, and the mechanical properties of the basalt fiber are improved by ion exchange to obtain a basalt fiber composite material.
[0006] In order to achieve the above-mentioned object, the present invention provides a basalt fiber composite material with bismuth oxyhalide grown on the surface, and a preparation method and application thereof, comprising: step 1, using water or low-carbon alcohol as a solvent, respectively preparing 3+ A solution with a cation of K + , Rb + or Cs + The B solution whose anion is a halogen ion is stirred for 30 to 60 minutes respectively; the molar concentration range of the A solution is 0.0857 to 0.2571 mol / L, the molar concentration range of the B solution is 0.0857 to 0.2571 mol / L, and the carbon number of the low-carbon alcohol does not exceed 5; step 2, slowly adding the B solution obtained in step 1 to the A solution, and stirring for 30 to 60 minutes to obtain a precursor solution; step 3, placing the cleaned basalt fiber in a hydrophilic surfactant solution, refluxing in a water bath at 60 to 80° C. for 4 to 8 hours for hydrophilic modification, and obtaining a hydrophilic basalt fiber; step 4, placing the precursor solution and the hydrophilic basalt fiber together in a high-pressure reactor, keeping warm at 120 to 180° C. for 4 to 16 hours, and preparing a basalt fiber composite material with surface-grown bismuth oxyhalide.
[0007] In one embodiment, the low-carbon alcohol in step 1 is any one of ethanol, ethylene glycol, isopropanol and glycerol.
[0008] In one embodiment, the A solution in step 1 is Bi(NO 3 ) 3 ·5H 2 O、BiCl 3 or NaBiO 3 ·2H 2 O configured.
[0009] In one embodiment, the B solution in step 1 is prepared using KI, KBr, KCl, RbI, RbBr, RbCl, CsI, CsBr or CsCl.
[0010] In one embodiment, the ratio of the solution A to the solution B in step 2 is in the range of 1:1 to 1:3.
[0011] In one embodiment, the cleaned basalt fiber in step 3 is cleaned by using acetone solution and deionized water.
[0012] In one embodiment, the pressure in the high-pressure reactor in step 4 is not less than 0.1 MPa.
[0013] In one embodiment, the tensile strength of the basalt fiber composite material in step 4 is increased by 5 to 90%, and the elastic modulus is increased by 5 to 80%.
[0014] A basalt fiber composite material with bismuth oxyhalide grown on the surface is prepared by adopting the above method.
[0015] An application of a basalt fiber composite material with bismuth oxyhalide grown on the surface. The basalt fiber composite material with bismuth oxyhalide grown on the surface is used for photocatalytic degradation.
[0016] Compared with the prior art, the present invention has the advantages of directly growing nano-sized bismuth oxyhalide on the surface of basalt fiber by hydrothermal method or solvothermal method to obtain basalt fiber composite material. In addition, during the growth of bismuth oxyhalide, the large radius K + (Rb + or Cs + ) ions and the smaller radius Na in basalt fibers + Ions exchange under high temperature and high pressure, which further makes basalt fiber composites have higher mechanical properties, thereby expanding the application of basalt fiber in environmental management, composite materials and other functional properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0018] Figure 1 It is a schematic diagram of the process of preparing a basalt fiber composite material in an embodiment of the present invention. DETAILED DESCRIPTION
[0019] The embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0020] The following describes the implementation methods of the present application through specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that, in the absence of conflict, the following embodiments and the features in the embodiments can be combined with each other. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.
[0021] It should be noted that various aspects of the embodiments within the scope of protection of the present invention are described below. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present application, it should be understood by those skilled in the art that an aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number and aspect described herein can be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein can be used to implement this device and / or practice this method.
[0022] It should also be noted that the illustrations provided in the following embodiments are only schematic illustrations of the basic concept of the present application. The drawings only show components related to the present application rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.
[0023] Additionally, in the following description, specific details are provided to facilitate a thorough understanding of the examples. However, it will be understood by those skilled in the art that the aspects described may be practiced without these specific details.
[0024] like Figure 1 As shown, the embodiment of the present application provides a method for preparing a basalt fiber composite material, comprising the following steps:
[0025] Step 1: using water or low carbon alcohol as solvent, respectively preparing 3+ A solution with a cation of K + , Rb + or Cs +The B solution whose anion is a halogen ion is stirred for 30 to 60 minutes respectively; the molar concentration range of the A solution is 0.0857 to 0.2571 mol / L, and the molar concentration range of the B solution is 0.0857 to 0.2571 mol / L.
[0026] In one embodiment, the molar concentration ratio of solution A to solution B is 1:1 to 1:3.
[0027] Step 2: slowly add the solution B obtained in step 1 to the solution A, and stir for 30 to 60 minutes to obtain a precursor solution.
[0028] The purpose of slowly adding solution B to solution A is to control the reaction rate, avoid local supersaturation, and improve the uniformity of the reaction.
[0029] Step 3: placing the cleaned basalt fiber in a hydrophilic surfactant solution, and refluxing in a water bath at 60-80° C. for 4-8 hours to perform hydrophilic modification to obtain hydrophilic basalt fiber.
[0030] The basalt fiber is cleaned with an acetone solution and / or deionized water to obtain a treated basalt fiber. The basalt fiber here can be commercially available, such as produced by China Fiber New Material Technology (Chengde) Co., Ltd.; it can also be prepared in the laboratory according to the basalt fiber raw material formula. If the surface of the basalt fiber is coated with a wetting agent, it is necessary to use an acetone solution to remove the glue and then clean it with deionized water. If the surface of the basalt fiber is not coated with a wetting agent, it can be directly cleaned with deionized water.
[0031] The principle of modification is: hydrophilic surfactant has excellent hydrophilicity, and its hydrophilicity can be improved by forming a layer of hydrophilic polymer chains on the surface of basalt fiber. In order to provide more active sites on the surface of basalt fiber and grow more bismuth oxyhalide. The surfactant can be polyethylene glycol, sodium dodecyl sulfate or dodecyl trimethyl ammonium bromide. The hydrophilic group of the surfactant is -OH, and the concentration range of the surfactant is 30-50g / L.
[0032] Step 4: Place the precursor solution and the hydrophilic basalt fiber into a high-pressure reactor together, keep the temperature at 120-180° C. for 4-16 hours, and prepare a basalt fiber composite material with bismuth oxyhalide grown on the surface.
[0033] The principle of bismuth oxyhalide growth is:
[0034] (1) Dissolution of reactants: Prepare the mixture containing Bi 3+ A solution with a cation of K + , Rb + or Cs +and solution B in which the anion is a halogen ion;
[0035] (2) Nucleation: On the surface of basalt fiber, ions aggregate under specific conditions to form the initial nuclei of bismuth oxyhalide;
[0036] (3) Deposition growth: As the reaction proceeds, more bismuth oxyhalide ions are deposited on the surface of the core, forming a continuous growth.
[0037] There is Na in the internal structure of basalt fiber + ions, will contain a lot of K + , Rb + or Cs + The precursor solution of K ions is placed into a high-pressure reactor, which effectively promotes the + (Rb + or Cs + ) / Na + Ion exchange is used to improve the mechanical properties of basalt fiber substrate materials.
[0038] A basalt fiber composite material with bismuth oxyhalide grown on the surface is prepared by adopting the above method.
[0039] The above method directly grows nano-sized bismuth oxyhalide on the surface of basalt fiber by hydrothermal method or solvothermal method, and during the growth of bismuth oxyhalide, K in the precursor solution + , Rb + or Cs + Ions and Na in basalt fibers + Ions exchange under high temperature and high pressure, which further makes basalt fiber composites have higher mechanical properties, thereby expanding the application of basalt fiber in environmental management, composite materials and other functional properties.
[0040] In one embodiment, the treated basalt fiber is cleaned by using an acetone solution and deionized water. The acetone solution can remove the wetting agent on the basalt fiber, and can also remove grease and dust on the surface of the basalt fiber. The acetone solution can be prepared by acetone and water. In one embodiment, acetone and water can be mixed in a volume ratio of 1:1 to obtain an acetone aqueous solution with a concentration of 50%.
[0041] In one embodiment, solution A is made of Bi(NO 3 ) 3 ·5H 2 O or BiCl 3 or NaBiO 3 ·2H 2 O is prepared in a solvent.
[0042] In one embodiment, solution B is prepared by using KI, KBr, KCl, RbI, RbBr, RbCl, CsI, CsBr or CsCl in a solvent.
[0043] In one embodiment, the molar ratio of solution A to solution B in step 2 is in the range of 1:1 to 1:3.
[0044] In one embodiment, when the filling degree of the autoclave is 70%, the pressure inside the autoclave is not less than 0.1 MPa. Specifically, when water is used as the solvent, the pressure inside the autoclave is 0.4-1 MPa (120-180°C); when ethylene glycol is used as the solvent, the pressure inside the autoclave is 0.2-0.8 MPa (120-180°C); when ethanol is used as the solvent, the pressure inside the autoclave is 0.6-9 MPa (120-180°C); when isopropanol is used as the solvent, the pressure inside the autoclave is 1.2-18 MPa (120-180°C); when glycerol is used as the solvent, the pressure inside the autoclave is 0.1-1.8 MPa (120-180°C).
[0045] In one embodiment, the tensile strength of the basalt fiber composite material in step 4 is increased by 5-90% and the elastic modulus is increased by 5-80% compared with the basalt fiber in step 3. For example, the tensile strength and elastic modulus of the basalt fiber composite material are tested by a fiber tensile tester. The tensile strength range of the hydrophilic basalt fiber in step 3 is 1600-2900Mpa, and the elastic modulus range is 54-110Gpa. The tensile strength range of the basalt fiber composite material in step 4 is 2000-3200Mpa, and the elastic modulus range is 80-130Gpa.
[0046] An application of a basalt fiber composite material with bismuth oxyhalide grown on the surface, wherein the basalt fiber composite material with bismuth oxyhalide grown on the surface is used for photocatalytic degradation. In one embodiment, the basalt fiber composite material with bismuth oxyhalide grown on the surface can be tested for mechanical properties and photocatalytic degradation properties. For example, the prepared basalt fiber composite material with bismuth oxyhalide grown is woven into a 3×3 cm 2 The material was tested for photocatalytic degradation performance and it was found that Rhodamine B (10 mg / L, 50 mL) could be degraded by 10% to 85% within 120 min.
[0047] Example 1
[0048] A method for preparing a basalt fiber composite material comprises the following steps:
[0049] Step 1: 9 mmol of Bi(NO 3 ) 3 ·5H 2O was dissolved in 35 mL of ethylene glycol solution, recorded as solution A, and then 9 mmol of KI was dissolved in 35 mL of ethylene glycol solution, recorded as solution B, and each was stirred for 30 min.
[0050] Reactants dissociate:
[0051] 1. Bismuth nitrate [Bi(NO)·5HO] dissociates into Bi 3+ and NO 3 - :
[0052] Bi(NO)·5H 2 O→Bi 3+ +3NO - +5H 2 O
[0053] 2. Potassium iodide (KI) dissociates into K + and I - :
[0054] KI→K + +I -
[0055] Step 2: Slowly add the solution B obtained in step 1 to the solution A and stir for 30 minutes to obtain a precursor solution.
[0056] Step three: using acetone solution and deionized water to remove the wetting agent, grease and dust on the surface of the basalt fiber to obtain cleaned basalt fiber.
[0057] Step 4: Place the cleaned basalt fiber in step 3 in a 50g / L polyethylene glycol solution and reflux in a water bath at 60°C for 4 hours to perform hydrophilic modification to obtain hydrophilic basalt fiber. The tensile strength and elastic modulus of the hydrophilic basalt fiber were tested by a fiber strength and elongation tester, and the specific values were 2338Mpa and 84.26GPa respectively. The hydrophilic basalt fiber was woven into a 3×3cm 2 The material was tested for photocatalytic degradation performance and could only degrade 5% of Rhodamine B (10 mg / L, 50 mL) within 120 minutes.
[0058] Step 5: Place the precursor solution obtained in step 2 and the hydrophilic basalt fiber obtained in step 4 into a 100 mL high-pressure reactor, keep the temperature at 140° C. for 8 hours, and obtain a basalt fiber composite material with BiOI grown on the surface.
[0059] 1.Bi 3+ With I- and oxygen ions in the solution to form bismuth iodide (BiOI) precipitate:
[0060] Bi 3++I - +O 2- →BiOI (precipitation)
[0061] 2. Ion exchange equation:
[0062] Na + 玄武岩纤维 +K + 溶液 →K + 玄武岩纤维 +Na + 溶液
[0063] Among them, O 2- It mainly comes from Bi(NO 3 ) 3 ·5H 2 O's crystal water or -OH in ethylene glycol solvent.
[0064] The tensile strength and elastic modulus of the basalt fiber composite material with BiOI grown on the surface were tested by a fiber tensile tester, and the specific values were 2641Mpa and 101.85GPa, which were greater than 2338Mpa and 84.26Gpa in step 4, and increased by 12.59% and 20.89 respectively compared with step 4. The prepared composite material was woven into a 3×3cm 2 The photocatalytic degradation performance test of the material showed that Rhodamine B (10 mg / L, 50 mL) could be degraded by 81% within 120 min, and the degradation efficiency was much greater than the 5% in step four.
[0065] Comparative Example 1
[0066] A method for preparing a basalt fiber composite material comprises the following steps:
[0067] Step 1: 9 mmol of Bi(NO 3 ) 3 ·5H 2 O was dissolved in 35 mL of ethylene glycol solution, recorded as solution A, and then 9 mmol of NaI was dissolved in 35 mL of ethylene glycol solution, recorded as solution B, and each was stirred for 30 min.
[0068] Step 2: Slowly add the solution B obtained in step 1 to the solution A and stir for 30 minutes to obtain a precursor solution.
[0069] Step three: using acetone solution and deionized water to remove the wetting agent, grease and dust on the surface of the basalt fiber to obtain cleaned basalt fiber.
[0070] Step 4: Place the cleaned basalt fiber obtained in step 3 in a 50g / L polyethylene glycol solution and reflux in a water bath at 60°C for 4h to perform hydrophilic modification to obtain hydrophilic basalt fiber. The tensile strength and elastic modulus of the hydrophilic basalt fiber were tested by a fiber strength and elongation tester, and the specific values were 2338Mpa and 84.26GPa, respectively. The hydrophilic basalt fiber was woven into a 3×3cm 2 The material was tested for photocatalytic degradation performance and could only degrade 5% of Rhodamine B (10 mg / L, 50 mL) within 120 minutes.
[0071] Step 5: Place the precursor solution obtained in step 2 and the hydrophilic basalt fiber obtained in step 4 into a 100 mL high-pressure reactor, keep warm at 140°C for 8 hours, and obtain a basalt fiber composite material with BiOI grown on the surface. The tensile strength and elastic modulus of the basalt fiber composite material with BiOI grown on the surface were tested by a fiber strength and elongation tester, and the specific values were 1803Mpa and 74.98GPa, which are less than 2338Mpa and 84.26GPa in step 4, and are reduced by 22.88% and 11.01% respectively compared with step 4. The prepared composite material is woven into a size of 3×3cm 2 The photocatalytic degradation performance test of the material showed that Rhodamine B (10 mg / L, 50 mL) could be degraded by 69% within 120 min. The degradation efficiency was much higher than 5% in step 4 and slightly lower than 81% in step 5 of Example 1.
[0072] According to the experimental results of Example 1 and Comparative Example 1, this example has a significant enhancement effect on the mechanical properties of the basalt fiber substrate material, and the prepared composite material has significant photocatalytic degradation performance.
[0073] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed in the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing a basalt fiber composite material with bismuth oxyhalide grown on the surface, characterized in that: include: Step 1: using water or low carbon alcohol as solvent, respectively preparing 3+ A solution with a cation of K + , Rb + or Cs + The anions of the solutions B are halogen ions, and each solution is stirred for 30 to 60 minutes; the molar concentration of the solution A is in the range of 0.0857 to 0.2571 mol / L, and the molar concentration of the solution B is in the range of 0.0857 to 0.2571 mol / L; the carbon number of the low-carbon alcohol does not exceed 5; Step 2, slowly adding the B solution obtained in step 1 to the A solution, and stirring for 30 to 60 minutes to obtain a precursor solution; Step 3, placing the cleaned basalt fiber in a hydrophilic surfactant solution, and refluxing in a water bath at 60 to 80° C. for 4 to 8 hours to perform hydrophilic modification, thereby obtaining a hydrophilic basalt fiber; Step 4: placing the precursor solution and the hydrophilic basalt fiber into a high-pressure reactor, and keeping the temperature at 120-180° C. for 4-16 hours to prepare a basalt fiber composite material with bismuth oxyhalide grown on the surface.
2. The preparation method according to claim 1, characterized in that: The low-carbon alcohol in step 1 is any one of ethanol, ethylene glycol, isopropanol and glycerol.
3. The preparation method according to claim 1, characterized in that: The solution A in step 1 is prepared by using Bi(NO3)3·5H2O, BiCl3 or NaBiO3·2H2O.
4. The preparation method according to claim 1, characterized in that: The B solution in step 1 is prepared using KI, KBr, KCl, RbI, RbBr, RbCl, CsI, CsBr or CsCl.
5. The preparation method according to claim 1, characterized in that: The ratio of the solution A to the solution B in step 2 is in the range of 1:1 to 1:
3.
6. The preparation method according to claim 1, characterized in that: The cleaned basalt fiber is obtained by cleaning the basalt fiber with an acetone solution and deionized water.
7. The preparation method according to claim 1, characterized in that: The pressure in the high-pressure reactor in step 4 is not less than 0.1 MPa.
8. A basalt fiber composite material with bismuth oxyhalide grown on the surface, characterized in that: The basalt fiber composite material with bismuth oxyhalide grown on the surface is prepared by the method described in any one of claims 1 to 7.
9. Application of a basalt fiber composite material with bismuth oxyhalide grown on the surface, characterized in that: The basalt fiber composite material with bismuth oxyhalide grown on the surface as claimed in claim 8 is used for photocatalytic degradation.
Citation Information
Patent Citations
Nitrated carbon fiber loaded bismuth oxyhalide nanoflower and preparation method of nanoflower
CN103920508A
Photocatalytic purification material based on rock wool fiber
CN114797909A